1981
DOI: 10.1079/bjn19810012
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acid deficiency and evidence for arachidonate synthesis in the cat

Abstract: It has been suggested that the cat is unable to convert dietary linoleic acid to arachidonic acid (Rivers et al. 1975;Hassam et al. 1977). Studies by Sinclair et al. (1979) demonstrated that the cat has a deficiency in the synthesis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Although the genome sequence is incomplete, we found partial Fads1 and Fads4 sequences in the cat genome, but no orthologues of Fads2 or Fads3 (L Filipe C Castro, unpublished). These findings are consistent with previous biochemical characterizations, in particular, the apparent absence of Δ6 activity in comparison to presence of Δ5 activity in domestic cat ( Felix catus ) [23], [24]. In the tetrapod clade, we demonstrated that a large and unique independent expansion of the Fads1 lineage in chicken (three genes) and green anole (five genes) has taken place but, at present, with no clues on possible functional impacts (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Although the genome sequence is incomplete, we found partial Fads1 and Fads4 sequences in the cat genome, but no orthologues of Fads2 or Fads3 (L Filipe C Castro, unpublished). These findings are consistent with previous biochemical characterizations, in particular, the apparent absence of Δ6 activity in comparison to presence of Δ5 activity in domestic cat ( Felix catus ) [23], [24]. In the tetrapod clade, we demonstrated that a large and unique independent expansion of the Fads1 lineage in chicken (three genes) and green anole (five genes) has taken place but, at present, with no clues on possible functional impacts (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, 18:2(n-6) would be elongated to 20:2(n-6) and then desaturated at the A8 position to yield 20:3(n-6), whilst 18:3(n-3) would proceed in a similar fashion via 20:3(n-3) to 20:4(n-3). In cats, which are frequently considered as being incapable of converting 18:2(n-6) to 20:4(n-6) (Rivers et al 1975;Hassam et al 1977), it has been proposed that a limited conversion can actually occur via A8 and A5 desaturases acting sequentially (Sinclair et al 1981). The predatory nature of the pike makes it an aquatic counterpart of the cat and similarities in PUFA metabolism may occur.…”
Section: Incorporation Of Radiolabelled Pufamentioning
confidence: 99%
“…By contrast, diets containing 50g safflower oil plus 300 g hydrogenated beef tallow (6.7 % energy as linoleate)/kg prevented all clinical symptoms except reproduction problems in females (MacDonald et al 1983b). Workers in Australia (Sinclair et al 1979(Sinclair et al , 1981McLean & Monger, 1989) reported that cats maintained for up to 8 years on diets containing 50g safflower oilkg did not suffer the severe symptoms reported by Rivers and his colleagues (Rivers & Frankel, 1980). These cats appeared normal except for some dulling of hair coats and a general inability of females to produce more than two litters.…”
Section: Essential Fatty Acids In Cats: Lack Of A-6 Desaturationmentioning
confidence: 99%
“…The existence of a A-8 desaturase (Fig. 3), although suggested as an alternative pathway for the formation of A 8,11,14-20:3 and AA (Sinclair et al 1981) has not been established. If it were present in cats to any considerable degree, AA synthesis from LA might occur by this alternative pathway.…”
Section: A-8 Desaturase Enzymesmentioning
confidence: 99%
See 1 more Smart Citation